1976
DOI: 10.1139/y76-077
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral studies on the enantiomers of butaclamol demonstrating absolute optical specificity for neuroleptic activity

Abstract: Butaclamol is a member of a new chemical class for which antipsychotic activity in humans has been demonstrated. Butaclamol, a racemate, has been resolved into its optical isomers and a separation of activities was found to occur between the (+) and (-) enantiomers. The present experiments show that at doses ranging from 0.1 to 0.3 mg/kg the (+) enantiomer abolished amphetamine-induced (a) stereotyped behavior and (b) rotational behavior in rats with unilateral lesions in the substantia nigra. It also inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Drugs. Two drugs, pimozide (Janssen Pharmaceuticals) and (+)-butaclamol (Ayerst Laboratories), were used to examine the effects of dopamine receptor blockade (Andfo, Butcher, Corrodi, Fuxe, & Ungerstedt, 1970;Creese, Burt, & Snyder, 1976;Lippman & Pugsley, 1975;Voith & Cummings, 1976;Voith & Herr, 1975). The effects of norepinephrine receptor blockade were examined with phenoxybenzamine (Smith Kline & French Canada, Ltd.), an agent that blocks central receptors of the a-noradrenergic type (Andto & Strombom, 1974;Nickerson & Collier, 1975).…”
Section: Methodsmentioning
confidence: 99%
“…Drugs. Two drugs, pimozide (Janssen Pharmaceuticals) and (+)-butaclamol (Ayerst Laboratories), were used to examine the effects of dopamine receptor blockade (Andfo, Butcher, Corrodi, Fuxe, & Ungerstedt, 1970;Creese, Burt, & Snyder, 1976;Lippman & Pugsley, 1975;Voith & Cummings, 1976;Voith & Herr, 1975). The effects of norepinephrine receptor blockade were examined with phenoxybenzamine (Smith Kline & French Canada, Ltd.), an agent that blocks central receptors of the a-noradrenergic type (Andto & Strombom, 1974;Nickerson & Collier, 1975).…”
Section: Methodsmentioning
confidence: 99%
“…(+)-Butaclamol is an effective antipsychotic agent but ( -)-butaclamol is devoid of this activity. 18 The only published method for analysis of racemic butaclamol in serum is by TLC -fluorometric induction. The method involved cyclohexane extraction of serum samples followed by TLC of the concentrated extracts.…”
mentioning
confidence: 99%
“…It has been shown that in this series 1 neuroleptic activity is associated with 4a,13b-trans and 3(OH),13b(H)-trans relative configurations1,4,12 and that only the enantiomers having 3S,4aS,13bS absolute configurations are active. 4,5,12 We have described the qualitative and quantitative changes in neuroleptic activity which result from altering the bulky substituent at position 3,1,2 by introducing a chlorine substitutent at various positions on rings A and C3, and, in the following paper of this issue,13 from making molecular modifications in the rings A/B region.…”
mentioning
confidence: 99%
“…16 Reduction of 2 with sodium borohydride gave a 73% yield of the secondary alcohol 4, while reduction with lithium tri-sec-butylborohydride17 afforded 66% of the epimeric alcohol 5. The configurational assignments for Scheme I HO 4 [3(H),13b(H)-trans] 5 [3(H),13b(H)-cis] 2 (4a,13b-trans) 3 (4a,13b-cis) 5, as 3(H),13b(H)-cis (hydroxyl axial), and for 4, therefore, as 3(H),13b(H)-trans (hydroxy equatorial), are based on the report18 that the bulky tri-sec-butylborohydrides reduce cyclohexanones by virtually exclusive attack by the reagent from the equatorial side to produce axial alcohols.…”
mentioning
confidence: 99%